Hijabers' Identity Construction as Muslimah through Consumption Structures in Food Lifestyle - Qurrantain, Nadia; Prasetyo, Bambang Dwi; Prianti, Desi Dwi (Technium Social Sciences Journal, 2021)
The choice of a person's adopted lifestyle can define his social identity through the consumption structure. This research aims to describe how consumption structure in food lifestyle plays a role in identity construction of Muslimah by referring to Pierre Bourdieu's theory. This study discusses the construction of identity as Muslimah carried out by the Hijabersmom Community as one of the biggest Islamic-based communities in Indonesia. This study used a transformative paradigm by online questionnaires and interviews for data collection. The results show their identity as a Muslimah is represented through the consumption of halal-labeled food, paying attention to the composition of foods other than those containing pork and those forbidden by Islam, choosing places to eat that are comfortable for discussing and good for taking pictures, wearing fashionable outfits by using dress codes. The construction of Muslimah identity through this consumption structure is formed due to several factors such as habitus, ideology/religious structure, and this community doctrine. For further research, the researcher suggests conducting research related to the construction of identity as indicated by the expansion of the object of research which is not limited to a religious perspective.